Faktor-Faktor yang Mempengaruhi Minat Menggunakan Dompet Digital - Heratiana, Novita; Wijayanti, Anita; Nur Rois, Dimas Ilham (Transpublika Publisher, 2025)
Advancements in financial technology have increased the popularity of digital wallets as a convenient and efficient transaction tool. Digital wallets are programs that utilize advanced technology to facilitate online payments for users, eliminating the need for cash or physical cards. This study aims to examine how ease of use, convenience, and perceived risk influence people's interest in using digital wallets. A quantitative research approach was employed, with the study population consisting of individuals who use the DANA digital wallet application in Indonesia. The research sample comprised 100 participants, with the sample size determined using Slovin’s formula. The sampling method applied was purposive sampling. Data analysis was conducted using multiple linear regression with SPSS 22.0 software. The findings of this study indicate that ease of use plays a significant role in increasing interest in digital wallet usage. The simplicity of use greatly influences users' enthusiasm for adopting digital wallets, while convenience is also crucial in shaping interest. Conversely, perceived risk has a minimal impact on users' interest in using digital wallets, with a negative connotation. These findings can be beneficial for fintech developers in enhancing user experience with digital wallet services and serve as a foundation for further research on factors influencing digital wallet adoption.